(untitled) (Collection of research papers «ECONOMIC STRATEGY AND PROSPECTS OF TRADE AND SERVICES SECTOR DEVELOPMENT», 2025)
The article examines the specific features of implementing the open innovation concept in Ukrainian food industry enterprises. Given the growing role of innovation-driven interaction and inter-firm cooperation in ensuring competitiveness, an assessment was conducted of the activity level of food industry enterprises in adhering to the principles of open innovation. The study compares the indicators of innovation activity in the food industry with similar indicators of innovation-active enterprises across the economy and by types of economic activity. For a comprehensive evaluation, indicators were calculated that reflect the scale of open innovation adoption, the share of employees involved in innovation activities, labour productivity levels, and the volume of sold products. The analytical basis of the study was formed using data from the State Statistics Service of Ukraine. The results of the comparative analysis indicate that food industry enterprises demonstrate a relatively high level of inter-firm cooperation and are active users of external sources of knowledge, technologies, and partnership-based interactions. Compared to an average innovation-active enterprise and firms from other sectors, the food industry is characterised by broader application of open innovation principles. At the same time, it was found that the share of employees engaged in innovation activities, as well as labour productivity in innovation-active food enterprises, is lower than in more technologically intensive industries. The findings highlight the presence of structural constraints in the development of the innovation potential of food enterprises and underscore the need to modernise production processes, strengthen human resource capacity, and enhance institutional support to foster sustainable open innovation models.